Development and pilot of an international survey: 'Radiation Therapists and Psychosocial Support'. - Elsner, K.; Naehrig, D.; Halkett, Georgia; Dhillon, H. (John Wiley & Sons, 2018)
INTRODUCTION: Up to one third of radiation therapy patients are reported to have unmet psychosocial needs. Radiation therapists (RTs) have daily contact with patients and can provide daily psychosocial support to reduce patient anxiety, fear and loneliness. However, RTs vary in their values, skills, training, knowledge and involvement in providing psychosocial support. The aims of this study were to: (1) develop an online survey instrument to explore RT values, skills, training and knowledge regarding patient anxiety and psychosocial support, and (2) pilot the instrument with RT professionals to assess content validity, functionality and length. METHOD: An online cross-sectional survey, titled 'Radiation therapists and psychosocial support' was developed. Items included patient vignettes, embedded items from RT research, and the Professional Quality of Life Scale (ProQOL5). Four radiation oncology departments volunteered to pilot the survey; each nominated four RT staff to participate. Survey data were analysed descriptively and qualitative feedback grouped and coded to determine whether the survey needed to be refined. RESULTS: Thirteen of sixteen RTs completed the pilot survey and feedback form. Median time to completion was 35 mins, with 54% of respondents stating this was too long. Respondents reported content, questions and response options were relevant and appropriate. Feedback was used to: refine the survey instrument, minimise responder burden and drop out and improve functionality and quality of data collection. CONCLUSION: This pilot of the 'Radiation therapists and psychosocial support' survey instrument demonstrated content validity and usability. The main survey will be circulated to a representative sample of RTs for completion.